MENGUPAS KONSEP DAN MODEL PENDIDIKAN ISLAM AYAH PADA ANAK PEREMPUAN DI ERA SOCIETY 5.0 PERSPEKTIF HADIST NABI - maulaya, Rosendah Dwi; Rochmat, Cecep Sobar; Alamin, Nurul Salis (Rausyan Fikr : Jurnal Pemikiran dan Pencerahan, 2024)
Education for girls is essential in the era of society 5.0. Because, the character and behavior of women are often eroded by the progress of the times. Not infrequently, physically and morally, women are also victims of crime in this era. Advanced education that talks about character and life skills has been discussed in many studies, but no one has spoken explicitly about the concept and model of a father's education for his daughters. This study aims to explore the concepts and models of father-in-daughter education from the perspective of the Prophet's Hadith that are relevant to be applied in the era of society. Systematic Literature Review is the research method, so this study only requires secondary data. The research results are three hadiths discussing how to reconstruct the concept and ideal model of education of a father and his daughter. The first hadith emphasizes the role of fathers in the form of education and protection of daughters. The second hadith discusses patience in educating and fulfilling the physical and inner needs of one's daughter. The third hadith talks about glorifying girls and giving equal affection to boys. The conclusion that can be drawn from these three hadiths is that a father has a significant role in providing education, protection, and affection to daughters. This research implies that it is hoped that the reconstruction of educational concepts and models can be applied by a father in order to educate girls in this era of society 5.0.